Dutch and Portuguese in western Africa : empires, merchants and the Atlantic system, 1580-1674 - Silva, Filipa Ribeiro da, 1974- (Atlantic world (Leiden, Netherlands) ;, 2011)
By looking at Dutch and Portuguese systems of settlement and trade in Western Africa, this book sheds new light on the formation of Dutch and Portuguese imperial frames, forms of commercial organisation and their role on the seventeenth-century-Atlantic.